Pengaruh Psychological Comfort Terhadap Customer Satisfaction Coffee Shop di Kota Padang - Inka Prilla Syahreza; Nurmina Nurmina (Observasi : Jurnal Publikasi Ilmu Psikologi, 2024)
The development of the specialty coffee trade is currently transforming towards cafes or coffee shops. Coffee shops are in great demand among various age groups, from teenagers to adults. It is believed that psychological comfort can be found in coffee shops. This research is a quantitative study which aims to see the influence of Psychological Comfort on Customer Satisfaction of Coffee Shops in Padang City. The number of respondents in this study was 101 people using a purposive sampling technique. Data were analyzed using simple regression analysis. The research results show that there is an influence of Psychological Comfort on Coffee Shop Customer Satisfaction in Padang City.